Defining beauty : the body in ancient Greek art - Jenkins, Ian (London : The British Museum, 2015)
"Through word and image, this book explores the Greek portrayal of human character in art, along with sexual and social identity ... A series of lively introductory essays by leading scholars reveals aspects of how the Greeks themselves saw the human form both in life and art, following the reception of the reception of the Greek body into modern times. The book concludes with a reflection upon how the authentic Greek body came to be identified with the Parthenon sculptures, displacing all previous canons of Greek taste
Published on the occasion of the exhibition of the same name held at the British Museum, 26th March-5th July 2015.
boek